MICROSURGICAL AUTOGRAFTING FOR RECONSTRUCTION OF HEAD AND NECK ONCOLOGICAL DEFECTS. AN ANALYSIS OF 60 CASES - A. V. Karpenko; L. D. Roman; R. R. Sibgatullin; E. N. Belova; N. A. Evdokimova; D. N. Dzhalilov; V. G. Zolotyk; A. A. Bojko (Вестник хирургии имени И.И. Грекова)
The authors analyzed results of the free flap transfer in surgery of head and neck. 60 operations were performed since October 2006 till May 2012. Indications for using them were reconstruction of the mucosa of the oral cavity and the pharynx in 48 cases, the extensive defects of skin and soft tissues of the head and neck in 12 cases. All cases except 2 had the initial reconstruction. First 18 operations were performed with the binocular loupes, followed by using operating microscope. During the operations 42 radial skin-fascia flaps, 10 anterolateral femoral flaps, 5 thoracodorsal flaps, 1 anteromedial femoral flap, 1 scapular skin bone flap and 1 jejunal flap were used. During the early postoperative period one of the patients died (postoperative lethality 1.7%). Necrosis of flaps took place in 6 cases (5 radial skin-fascia flaps, 1 thoracodorsal flap). The causes of failures were assessed as arterial thrombosis (1 case), venous thrombosis (2 cases), postoperative infection (1 case). The exact cause in 2 cases couldn’t be determined. Thus, the total success in the given series of surgery was 88.9%.